Bond strength of an orthodontic adhesive system applied at several time intervals - Aguilar Ellis, Ana Gabriela; Ferreto Gutiérrez, Isabel; Rodriguez Wong, Laura; Cáceres Zapata, Hugo (Odovtos - International Journal of Dental Sciences, 2014)
<span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none;">The study was made to determine the bond strength to enamel of the self-etching bonding system Transbond Plus SE Primer (TBSEP) limited 3M ESPE, when applied at different time intervals after mixing its components, and before bonding the orthodontic brackets. A collection of 30 recently extracted premolars, caries and restoration free, were placed over acrylic resin for support. They were divided into three groups: CG: where brackets were bonded over the enamel surface using Transbond Plus Self-etching Primer ( limited 3M ESPE, St Paul, MN) as recommended by the manufacturer. In group EG1; 4 minutes after mixing the bonding agent components before bonding the brackets to the enamel. In group EG2; 4 hours after mixing TBSEP components, before bonding the brackets to the enamel. The adhesion strength may be affected by the time lapsed at the moment of placing the brackets. Specimens were stored in water at 37° C for 30 days before being tested for shear in a universal testing machine (Tinius Olsen H10KS) at a 0.1 cm/min crosshead speed. Data were recorded in MPa and analyzed using a one-way ANOVA calculated at a 0.05 significance level. <span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none;">Results: No statistical differences were found among groups. Bond strength of EG2 was less than 1 MPa different from the control group. The highest bond strength was from group EG1 which used the bonding system to bond the brackets 4 minutes after it was mixed. <span style="color: #000000; font-family: 'Times New Roman'; font-size: medium; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: auto; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: auto; word-spacing: 0px; -webkit-text-stroke-width: 0px; display: inline !important; float: none;">Conclusions: Waiting up to 4 hours after mixing TBSEP components does not affects the bond strength of the orthodontic bracket to enamel.